2015
DOI: 10.4329/wjr.v7.i7.180
|View full text |Cite
|
Sign up to set email alerts
|

Isolated renal hydatid presenting as a complex renal lesion followed by spontaneous hydatiduria

Abstract: Echinococcosis is a zoonotic disease. Liver is the most common site of involvement. Renal involvement is seen in 2% to 3% of patients. Computed tomography findings in renal hydatid typically include: a cyst with thick or calcified wall, unilocular cyst with detached membrane, a multiloculated cyst with mixed internal density and daughter cysts with lower density than maternal matrix. Rarely type IV hydatid cysts may mimic hypovascular renal cell carcinoma. We report a case of previously asymptomatic middle age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Similar to our case, Sidani et al, 5 and Singh et al, 2 reported cases of renal hydatid cyst in the middle-aged men. However, Choi et al, 6 and Bhaya et al, 7 reported renal hydatid cyst in older females. Chronic flank pain with urine colour changes was the most typical presentation in all the cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to our case, Sidani et al, 5 and Singh et al, 2 reported cases of renal hydatid cyst in the middle-aged men. However, Choi et al, 6 and Bhaya et al, 7 reported renal hydatid cyst in older females. Chronic flank pain with urine colour changes was the most typical presentation in all the cases.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic flank pain with urine colour changes was the most typical presentation in all the cases. 2,[5][6][7] Radiological imaging in all the cases misled the diagnosis by tagging it renal malignancy that came out to be hydatid cyst on histopathological examination. 2,[5][6][7] The classical CT findings for renal hydatid disease, including a cyst with the calcified wall, a detached membrane in a unilocular cyst, a multi-loculated cyst with daughter cysts, could not be recognized on initial CT scan reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) and computed tomography (CT) identify the loculated nature of the lesion and may demonstrate a floating membrane, which confirms the diagnosis. computed tomography is more sensitive than US imaging, evidenced by its ability to detect calcifications, it requires harmful ionizing radiation [8]. magnetic resonance imaging (MRI) is preferable since it delivers high-resolution images without this high dose of radiation, of importance in children [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hypointense rim and multi cystic appearance is distinctive in MRI which also delineates the anatomy well. Intravenous urogram should be done to rule out a communication with renal ductal system [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Renal hydatid may be seen as simple or complex renal cyst on imaging. 20 In this study renal hydatid patients were managed by nephrectomy. Nephron sparing procedures could not be done as the cysts involved the entire parenchyma with dysfunction of t he kidney.…”
Section: Discussionmentioning
confidence: 99%